2021
DOI: 10.1021/acsami.1c15428
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach of Compression Molding and Magnetic Attraction to Micropatterning of Magnetic Polydimethylsiloxane Composite Surfaces with Excellent Anti-Icing/Deicing Performance

Abstract: The accumulation of ice and contaminants on the surface of composite insulators will cause high energy consumption or even major hazards to power systems. In this work, the polydimethylsiloxane (PDMS) silicone rubber was modified by surface micropatterning and material compositing. Highly crosslinked poly­(cyclotriphosphazene-co-4,4′-sulfonyldiphenol) (PZS) was used to directly coat ferroferric oxide (Fe3O4) nanoparticles. The obtained core–shell Fe3O4@PZS microspheres were loaded with carbon nanotubes (CNTs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Compared with electro‐thermal heat techniques, solar energy as the renewable source is free and sustainable from nature. Recently, researchers investigated sun light (or artifical light) to replace electric power, and developed photo‐thermal promoted AIM by combining passive AIM (i.e., SHSs, [ 106 ] lubricating surfaces, [ 107–110 ] and other icephobic surfaces [ 111,112 ] ) ( Figure ) with active photo‐thermal heating with the help of various absorbers (i.e., Fe 3 O 4 , [ 107,108,113–115 ] candle soot, [ 12,116 ] carbon nanotubes (CNTs), [ 89,90,112,117–126 ] carbon nanofibers, [ 111 ] CNTs/Fe 3 O 4 @poly(cyclotriphosphazene‐co‐4,4′‐sulfonyldiphenol) (PZS), [ 127 ] cermet, [ 32 ] I 2 , [ 128 ] SiC, [ 129 ] polypyrrole (PPy), [ 98 ] melanin, [ 130 ] CNTs/SiO 2 , [ 131 ] Fe/candle soot, [ 106 ] Fe/Cu, [ 132 ] titanium nitride (TiN), [ 133,134 ] Ti 2 O 3 , [ 135 ] Au/TiO 2 , [ 66,136 ] Au/SiO 2 , [ 137 ] reduced graphene oxide (rGO), [ 138 ] graphite, [ 139 ] SiO 2 /CuFeMnO 4 , [ 140 ] MXene, [ 141 ] and black engineered aluminum [ 142,143 ] ) (See Table 3 ). Generally, the absorption capacity of these absorbers differs from one to another, and the photo‐thermal effect usually occurs under different light wavelengths, such as solar radiation, [ 107 ] near infrared irradiation, [ 89,108,118,129 ] and infrared irradiation (See Table 3).…”
Section: Photo‐thermal Promoted Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with electro‐thermal heat techniques, solar energy as the renewable source is free and sustainable from nature. Recently, researchers investigated sun light (or artifical light) to replace electric power, and developed photo‐thermal promoted AIM by combining passive AIM (i.e., SHSs, [ 106 ] lubricating surfaces, [ 107–110 ] and other icephobic surfaces [ 111,112 ] ) ( Figure ) with active photo‐thermal heating with the help of various absorbers (i.e., Fe 3 O 4 , [ 107,108,113–115 ] candle soot, [ 12,116 ] carbon nanotubes (CNTs), [ 89,90,112,117–126 ] carbon nanofibers, [ 111 ] CNTs/Fe 3 O 4 @poly(cyclotriphosphazene‐co‐4,4′‐sulfonyldiphenol) (PZS), [ 127 ] cermet, [ 32 ] I 2 , [ 128 ] SiC, [ 129 ] polypyrrole (PPy), [ 98 ] melanin, [ 130 ] CNTs/SiO 2 , [ 131 ] Fe/candle soot, [ 106 ] Fe/Cu, [ 132 ] titanium nitride (TiN), [ 133,134 ] Ti 2 O 3 , [ 135 ] Au/TiO 2 , [ 66,136 ] Au/SiO 2 , [ 137 ] reduced graphene oxide (rGO), [ 138 ] graphite, [ 139 ] SiO 2 /CuFeMnO 4 , [ 140 ] MXene, [ 141 ] and black engineered aluminum [ 142,143 ] ) (See Table 3 ). Generally, the absorption capacity of these absorbers differs from one to another, and the photo‐thermal effect usually occurs under different light wavelengths, such as solar radiation, [ 107 ] near infrared irradiation, [ 89,108,118,129 ] and infrared irradiation (See Table 3).…”
Section: Photo‐thermal Promoted Aimmentioning
confidence: 99%
“…Compared with electro-thermal heat techniques, solar energy as the renewable source is free and sustainable from nature. Recently, researchers investigated sun light (or artifical light) to replace electric power, and developed photo-thermal promoted AIM by combining passive AIM (i.e., SHSs, [106] lubricating surfaces, [107][108][109][110] and other icephobic surfaces [111,112] ) (Figure 7) with active photo-thermal heating with the help of various absorbers (i.e., Fe 3 O 4 , [107,108,[113][114][115] candle soot, [12,116] carbon nanotubes (CNTs), [89,90,112,[117][118][119][120][121][122][123][124][125][126] carbon nanofibers, [111] CNTs/Fe 3 O 4 @ poly(cyclotriphosphazene-co-4,4′-sulfonyldiphenol) (PZS), [127] cermet, [32] I 2 , [128] SiC, [129] polypyrrole (PPy), [98] melanin, [130] CNTs/SiO 2 , [131] Fe/candle soot, [106] Fe/Cu, [132] titanium nitride (TiN), [133,134] Ti 2 O 3 , [135] Au/TiO 2 , [66,136] Au/SiO 2 ,…”
Section: Photo-thermal Promoted Aimmentioning
confidence: 99%
“…Chen et al reported the synthesis of highly crosslinked poly(cyclotriphosphazene-co-4,4 -sulfonyldiphenol) (PZS) used to coat ferric oxide (Fe 3 O 4 ) nanoparticles directly and then were loaded with carbon nanotubes (CNTs) to get CNTs/Fe 3 O 4 @PZS as the photothermal magnetic filler. The PDMS/CNTs/Fe 3 O 4 @PZS surfaces with micron-scale truncated cones were prepared using compression molding and magnetic attraction [98].…”
Section: Moldingmentioning
confidence: 99%
“…Many methods have been used to construct surface micro/nano structures on silicone rubber surfaces, such as laser etching, 31 spray coating, 32 3D printing, 33 compression molding, 34 injection molding, 35 and soft lithography. 36 Among the above methods, laser etching is an industrial technology and is suitable for preparing rich micro/nanostructures on the surfaces of semiconductors, brittle materials, metals, polymers, ceramics and biomaterials.…”
Section: Introductionmentioning
confidence: 99%